USE OF DEUTERATED WATER AS A CONSERVATIVE ARTIFICIAL GROUNDWATER TRACER - Becker M.; Coplen T. (My University, 2001)
Conservative tracers are necessary to obtain groundwater transport velocities at the field scale. Deuterated water is an effective tracer for this purpose due to its similarity to water, chemical stability, non-reactivity, ease of handling and sampling, relatively neutral buoyancy, and reasonable price. Reliable detection limits of 0.1 mg deuterium/L may be obtained in field tests. A field example is presented in which deuterated water, bromide, and pentafluorobenzoic acid are used as groundwater tracers. Deuterated water appeared to be transported conservatively, producing almost identical breakthrough curves as that of other soluble tracers.
Keywords: TRACER TESTS; STABLE ISOTOPES; SOLUTE TRANSPORT; FRACTURED ROCKS; GROUNDWATER DENSITY; DEUTERIUM